Generation Z's Preferences for Messages of Happiness: A Quantitative Analysis of Material Attributes, Methods, Media, and Dai Characters - 'Ubudiyah, Farikhatul; Rohimi, Primi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2026)
The rise of digital da'wah has shifted religious learning for Generation Z to online platforms, but a clear understanding of their content preferences remains a research gap. This study employed a quantitative approach using conjoint analysis to map these preferences, particularly regarding the concept of da'wah with material on happiness. Data were collected from 180 valid student respondents (Gen-Z) and analyzed to evaluate a combination of four attributes: da'wah character, da'wah material, method, and digital media. The results revealed a definitive hierarchy of preferences, with da'wah material being the most determining factor (importance value: 36.178), followed by media (30.538), method (16.999), and da'wah character as the least influential (16.285). Audiences showed a strong preference for content on concrete social relationships, such as being a dutiful child (utility: 0.057) and having a good partner (0.026), and preferred thematic and advice-based methods over discussion. These findings fundamentally challenge the prevailing influencer-based marketing paradigm, demonstrating that for this demographic, the substance of the message is more important than the persona of the messenger. The study concludes that effective digital da'wah requires a strategic shift toward message-centric management, prioritizing practical, solution-oriented content delivered by competent and inspiring figures.